PENGEMBANGAN PROJECT BASED E-LEARNING DENGAN ANALISIS PIECES DAN DESAIN UML - Muhammad Fairuzabadi (Jurnal Dinamika Informatika, 2021)
Currently, the e-Learning application at PGRI Yogyakarta University still has several shortcomings, one of which is the absence of features for the project-based learning model (PjBL). PjBL is generally used for practical courses. This study aims to develop a project-based e-learning application at the University of PGRI Yogyakarta. The research method begins with data collection through interviews, observation and literature study. Furthermore, PIECES analysis, UML design and application feasibility tests were carried out using the black box test and alpha test methods. Based on the results of black box testing, it can be seen that the system can run well and has met the specifications on the problem boundary. Based on alpha testing, it was found that the interaction in using this application is very easy, the application interface design is very attractive, the functions of this application are complete, and the overall application performance is very good. Keyword: Project Based e-Learning, PIECES, UML